Cultivation of Family Medicinal Plants using the Verticulture Method as Efforts to Use Narrow Yard Land in Rawamangun, East Jakarta - Rizal Koen Asharo; Elsa Lisanti; Reni Indrayanti; Adisyahputra; Pinta Omas Pasaribu; Rizky Priambodo; Vina Rizkawati; Yulia Irnidayanti (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
The area of RW 01 Rawamangun, Pulogadung District, East Jakarta does not have an allocation of open  land, so there is a minimum of green yards. The technology introduced in this community service activity  is the cultivation of family medicinal plants in yards using the verticulture method. The purpose of this  community service activity is to convey information about the cultivation of family medicinal plants  through lectures, discussions, and direct practice of cultivating family medicinal plants in yards using the  verticulture method. Evaluation of participants' knowledge improvement was carried out by pre- and post test after counseling and cultivation practices. Skills participants are carried out when evaluating the  practice of cultivating medicinal plants in their yards. The results of the activity showed an increase in  basic knowledge regarding the types, benefits, and techniques of cultivating family medicinal plants from  technology. Family medicinal plant service activity is classified as successful and beneficial, due to  increased knowledge more than 60 in average test scoring. The skills evaluation showed that some  residents were able to plant and maintain family medicinal plants on a narrow plot of land using the  proper verticulture method. The results of the cultivation of these medicinal plants, apart from being one  of the real actions of plant greening, can also be in the form of powder products which can then be  consumed as a body health measure or sold.